Design and develop a web-based purchase order at PT. Password solusi sistem - Cyntya, Loren; Bani, Alexius Ulan; Sharyanto, Sharyanto (Journal of Engineering, Technology and Computing (JETCom), 2024)
PT PASSWORD SOLUSI SISTEM is a company that provides IT Infrastructure, System Integrator & Business Application solutions, including implementing, maintaining, and providing other value-added services to customers. This thesis describes the design and development of a web-based Purchase Order Information System for PT. Password Solusi Sistem. The research aims to address the current manual and error-prone purchase order input process. Through a web-based development approach, the system is designed to improve efficiency in handling purchase orders, expedite responses to emerging issues, and ultimately enhance customer satisfaction. The research results include a well-tested UI (User Interface) design and prototype of the information system application, demonstrating a valid level of success. With the implementation of this system, it is expected that PT. Password Solusi Sistem can more effectively and efficiently address purchase order issues, bringing significant benefits to the company and customers.